Development of stable Pickering emulsions/oil powders and Pickering HIPEs stabilized by gliadin/chitosan complex particles. Issue 6 (17th May 2017) - Yuan, D. B.; Hu, Y. Q.; Zeng, T.; Yin, S. W.; Tang, C. H.; Yang, X. Q.
Abstract : In this paper, we demonstrate the use of gliadin/chitosan complex particles (GCCPs) as particulate stabilizers of oil-in-water emulsions of natural oils and water. Abstract : In this paper, we demonstrate the use of gliadin/chitosan complex particles (GCCPs) as particulate stabilizers of oil-in-water emulsions of natural oils and water. For this purpose, we fabricated GCCPs through a facile anti-solvent procedure and demonstrated their usage in the formation of Pickering emulsions and Pickering high internal phase emulsions (HIPEs). The GCCPs can be used to produce surfactant-free o/w Pickering emulsions and Pickering HIPEs; unfortunately these emulsions were labile to coalescence. NaCl addition and/or pH regulation, and the combination were used to modify the surface wettability of the complex particles to achieve stable emulsions. The microstructures, e.g., interfacial frameworks, GCCP partition between the continuous phase and interfacial region, and the state of the droplets, of Pickering emulsions were visualized by confocal laser scanning microscopy (CLSM), confirming that the inclusion of NaCl and slightly adjusting pH toward 4.0 and/or 5.0 benefited the adsorption and accumulation of colloid particles at the droplet surface to form an engineered interfacial structure, bridging droplets together through a percolating layer of colloidal particles at the oil/water interface. A schematic representation for the formation route of the emulsions is proposed to relate the physical performance and rheological property with the interfacial structures and aggregate behaviors in the Pickering system stabilized by the complex particles. Interestingly, direct freeze-drying of the emulsions transformed unstable Pickering emulsions into stable oil powders. This study opens a promising route based on Pickering HIPEs or oil powders to structure liquid oils into solid-like fats without artificial trans -fat, which outlines new directions for future fundamental research.